1988
DOI: 10.1037/0033-2909.104.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Evolving conceptions of memory storage, selective attention, and their mutual constraints within the human information-processing system.

Abstract: The purpose of this review is to formulate a revised model of information processing that takes into account recent research on memory storage, selective attention, effortful versus automatic processing, and the mutual constraints that these areas place on one another. One distinctive aspect of the proposed model is the inclusion of two phases of sensory storage in each modality. The first phase extends sensation for several hundred milliseconds, whereas the second phase is a vivid recollection of sensation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

81
1,250
1
45

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,518 publications
(1,377 citation statements)
references
References 210 publications
(358 reference statements)
81
1,250
1
45
Order By: Relevance
“…The contents of working memory are often viewed as an activated subset of information from long-term memory, with the focus of attention determining what information becomes active (Cowan, 1988;Engle et al, 1999). Such a model does not require that the attentional controller, perhaps DLPFC, actually represents the information.…”
Section: Discussionmentioning
confidence: 99%
“…The contents of working memory are often viewed as an activated subset of information from long-term memory, with the focus of attention determining what information becomes active (Cowan, 1988;Engle et al, 1999). Such a model does not require that the attentional controller, perhaps DLPFC, actually represents the information.…”
Section: Discussionmentioning
confidence: 99%
“…The control of attention was an important element of early theories of information processing (e.g., Atkinson & Shiffrin, 1968) and is embodied in the central executive component of theoretical conceptions of WM (e.g., Baddeley, 1986;Cowan, 1988Cowan, , 1995. A great deal of recent research has converged on the importance of the control of attention in carrying out the standard type of WM task involving separate storage and processing components.…”
Section: Control Of Attentionmentioning
confidence: 99%
“…In contrast, in the conception of WM as a multi-component system (e.g., Baddeley, 1986;Baddeley & Logie, 1999), attention tended to be associated with executive control but not with storage per se; that storage was assumed to be automatic once the information was entered into it, and it was assumed to be time-limited instead of capacitylimited. Cowan (1988Cowan ( , 1995Cowan ( , 1999 advocated both attention-free and attention-dependent forms of storage, with only the attention-dependent forms limited in capacity per se. Broadbent (1975) suggested that there is a form of storage that is limited to 3 items.…”
Section: Scope Of Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus on process makes terms such as "top down" versus "bottom up" obsolete. In terms of conventional theory, the holographic account is, perhaps, closest to Cowan's (1988Cowan's ( , 1993 idea that STM is an activated subset of long-term memory. He postulated an attentional mechanism activates a subset of memory.…”
Section: Memory As a Hologrammentioning
confidence: 99%